Assessing risk indicators for dental caries in the primary dentition - Vanobbergen J, Martens L, Lesaffre E, Bogaerts K, Declerck D (Blackwell Synergy, 2001)
The aim of the present study was to assess indicators shown to be associated with the prevalence of caries in the primary dentition of 7-year-old Flemish schoolchildren.